CFD pre-study of Nozzle reactor for fast hydrothermal liquefaction. (December 2017) - Tran, Khanh-Quang; Håkansson, Love; Trinh, Thuat T.
Abstract: A CFD (computational fluid dynamics) model of Nozzle rector has been developed in ANSYS FLUENT for prediction of process parameters suitable for fast hydrothermal liquefaction. The model has been validated by comparing with the literature on the basis of residence time distribution (RTD). The preliminary results show that the mass flowrate ratio of hot and cold flows plays the most important role in establishing high heating rates in the reactor, assuming an adiabatic system boundary. Tests for pure water (viscosity = 0.001 Pa.s), the mass flowrate ratio of 60:20 (hot/cold, mil/min) gave very good mixing and thus high heating rate. Effect of the total mass flow on the temperature profile in the reactor was not significant. Cold flows with viscosity higher than 0.01 [Pa.s] resulted in poor mixings at the nozzle for the mass flowrate ratio of 60:20.